Subtype prediction in primary aldosteronism: measurement of circadian variation of adrenocortical hormones and 24‐h urinary aldosterone. (4th February 2016) - Kobayashi, Hiroki; Haketa, Akira; Ueno, Takahiro; Suzuki, Ryo; Aoi, Noriko; Ikeda, Yukihiro; Tahira, Kazunobu; Hatanaka, Yoshinari; Tanaka, Sho; Otsuka, Hiromasa; Abe, Masanori; Fukuda, Noboru; et al.
Summary: Objective: Currently, adrenal venous sampling (AVS) is the only reliable method to distinguish unilateral from bilateral hyperaldosteronism in primary aldosteronism (PA). However, AVS is costly and time‐consuming compared with simple blood tests. In this study, we conducted a retrospective study to determine whether circadian variation in plasma adrenocortical hormone levels (i.e. aldosterone, cortisol and ACTH) and a 24‐h urinary aldosterone could contribute to the clinical differentiation between unilateral hyperaldosteronism (UHA) and bilateral hyperaldosteronism (BHA). Design: In 64 patients who were diagnosed with PA and underwent AVS, 32 and 22 patients were diagnosed with UHA and BHA, respectively. Plasma adrenocortical hormone levels at 0:00, 6:00, 12:00 and 18:00 and 24‐h urinary aldosterone under a condition of 6 g daily dietary sodium chloride intake were measured. Results: Baseline plasma aldosterone concentration (PAC) and 24‐h urinary aldosterone level in patients with UHA were significantly higher than in patients with BHA, particularly at 6:00. The area under the ROC curve for PAC at 0:00, 6:00, 12:00 and 18:00 and 24‐h urinary aldosterone to discriminate UHA and BHA was 0·839 [95% confidence interval (CI); 0·73−0·95], 0·922 (95% CI; 0·85−1·00), 0·875 (95% CI; 0·78−0·97), 0·811 (95% CI; 0·69−0·93), 0·898 (95% CI; 0·81−0·99), respectively. Conclusions: PAC at different blood sampling times and 24‐h urinary aldosterone level may be diagnostically helpful in discriminating between UHA and BHA. We believe that these tests could reduce the number of unnecessary AVS procedures.